Three-Dimensional Cartilage Regeneration Using Engineered Cartilage Gel With a 3D-Printed Polycaprolactone Framework - Wu, Gaoyang; Lu, Lixing; Ci, Zheng; Wang, Yahui; Shi, Runjie; Zhou, Guangdong; Li, Shengli (Frontiers in Bioengineering and Biotechnology, 2022)
The feasibility of the three-dimensional (3D) cartilage regeneration technology based on the " steel (framework)-reinforced concrete (engineered cartilage gel, ECG)" concept has been verified in large animals using the decalcified bone matrix (DBM) as the framework, however, unstable source, large sample variation, and uncontrollable 3D shape of DBM greatly hindered the clinical translation of this technology. To further optimize the cartilage regeneration of the ECG-framework model, the current study explored the feasibility of replacing the DBM framework with a 3D-printable polycaprolactone (PCL) framework for supporting cartilage regeneration of ECG. The results demonstrated that the PCL framework showed good biocompatibility with ECG and achieved a high ECG loading efficiency similar to the DBM framework. Furthermore, PCL-ECG constructs caused a relatively milder inflammation-immune response in vivo than that of DBM-ECG constructs, which was further confirmed by in vitro macrophage activation experiment. More importantly, the PCL-ECG constructs successfully regenerated mature cartilage and basically maintained the original shape after 8 weeks of subcutaneous implantation. The quantitative analysis further revealed that the GAG and total collagen contents of regenerated cartilage in the PCL-ECG group were significantly higher than those in the DBM-ECG group. All these results indicated that the 3D-printed PCL framework, as a clinically approved biomaterial with multiple advantages in customized shape design, mechanical strength control, and standardized production, can serve as an excellent framework for supporting 3D cartilage regeneration of ECG, which provides a novel and feasible strategy for clinical translation of ECG-based 3D cartilage regeneration.